2020
DOI: 10.1021/jacs.0c09599
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduction of Cu Single Atoms Decorated on UiO-66-NH2 for Enhanced Photocatalytic Reduction of CO2 to Liquid Fuels

Abstract: Photocatalytic reduction of CO 2 to value-added fuels is a promising route to reduce global warming and enhance energy supply. However, poor selectivity and low efficiency of catalysts are usually the limiting factor of their applicability. Herein, a photoinduction method was developed to achieve the formation of Cu single atoms on a UiO-66-NH 2 support (Cu SAs/UiO-66-NH 2 ) that could significantly boost the photoreduction of CO 2 to liquid fuels. Notably, the developed Cu SAs/UiO-66-NH 2 achieved the solar-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
337
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 504 publications
(348 citation statements)
references
References 65 publications
10
337
0
1
Order By: Relevance
“…Wang et al reported an atomically dispersed Cu-based SACs deriving from the UiO-66-NH 2 through photoinduction method (Cu SAs/UiO-66-NH 2 ), illustrated in Figure 18a-c. [263] On the basis of the design principle, the UiO-66-NH 2 possesses amounts of NH 2 groups on the pores surface, facilitating the adsorption of Cu precursor via confined effect and coordinated effect. The further characterizations proved that the Cu atomically dispersed Cu SACs with an excellent CO 2 RR performance were obtained.…”
Section: Co 2 Rrmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al reported an atomically dispersed Cu-based SACs deriving from the UiO-66-NH 2 through photoinduction method (Cu SAs/UiO-66-NH 2 ), illustrated in Figure 18a-c. [263] On the basis of the design principle, the UiO-66-NH 2 possesses amounts of NH 2 groups on the pores surface, facilitating the adsorption of Cu precursor via confined effect and coordinated effect. The further characterizations proved that the Cu atomically dispersed Cu SACs with an excellent CO 2 RR performance were obtained.…”
Section: Co 2 Rrmentioning
confidence: 99%
“…a-g) Reproduced with permission. [263] Copyright 2020, American Chemical Society. h) TEM and i) HAADF-STEM image of FeN 4 /C.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The coupling between C 1 or other intermediates leads to the formation of C 2+ product such as ethylene (CH 2 CH 2 ), ethane (C 2 H 6 ), and ethanol (C 2 H 5 OH). [ 59,201 ] Semiconductors are commonly used in CO 2 RR, but suffer from the poor catalytic activity and selectivity owing to the large bandgap and low electron‐transfer efficiency. [ 201 ] Integrating plasmonic Cu nanomaterials with semiconductors has been proved to be a promising approach to lower the kinetic barriers of CO 2 RR and further enhance the photocatalytic activity.…”
Section: Localized Surface Plasmon Resonance‐mediated Reactions Over Cu‐based Plasmonic Catalystsmentioning
confidence: 99%
“…[ 59,201 ] Semiconductors are commonly used in CO 2 RR, but suffer from the poor catalytic activity and selectivity owing to the large bandgap and low electron‐transfer efficiency. [ 201 ] Integrating plasmonic Cu nanomaterials with semiconductors has been proved to be a promising approach to lower the kinetic barriers of CO 2 RR and further enhance the photocatalytic activity. For instance, recently, Atwater et al.…”
Section: Localized Surface Plasmon Resonance‐mediated Reactions Over Cu‐based Plasmonic Catalystsmentioning
confidence: 99%
“…9 [74] Ma 等 [73] [75] Fig. 10 Formation process and Structural characterizations of Mn-N2C2 [75] (a) Illustration of the formation of MnSAC, (b, c) HAADF-STEM images of MnSAC, (d) iR-corrected ORR polarization curves for MnSAC, CN, and 20% Pt/C, (e) Mn K-edge XANES and (f) FT EXAFS spectra of MnSAC and the references,(g) Atomic structure model for MnSAC Shang 等 [75] [80][81][82] 、 析氢反应(HER) [83][84][85] 、CO2 还原 [86][87][88][89][90] 、电还原合成氨 (NRR) [50,[91][92][93] 、硝酸盐还原反应(NO3-RR) [94] 以及其 它有机反应 [95][96] 等均显示出优秀的催化活性。 在电化学方面,SACs 可用作电极催化剂,提高 电化学储能装置的应用性能。以 SACs 作为正极的 质子交换膜燃料电池显示出优秀的功率密度 [97][98] 。 引入 SACs 的金属-空气电池展示出高开路电压以及 优秀的稳定性 [99][100][101][102][103][104][105] 。另外,SACs 还能够应用于锂 硫电池 [106][107] 、CO2 电池 [90] 以及染料敏化太阳能电 池 [108][109]…”
Section: 锰基 C-sacsunclassified